P 31 Long-term results with TPS (Transcranial Pulse Stimulation) treatment of Alzheimer's disease. (May 2022) - Novak, P.; Lohse-Busch, H.
Abstract : Introduction Low intensity shockwaves proofed to be efficient for the treatment of non-unions, tendon and muscular pain, wound healing, heart insufficiency, erectile dysfunction and since 1990 also neurological indications. The working principle is the mechanical stimulation of biological processes called mechanotransduction resulting in increased cell metabolism, release of nitric oxide (eNO) and numerous growth factors like VGEF, TGF, BNDF and others. There is also an anti-inflammatory effect, stimulation of stem cells and of the innate immune system. Transcranial Pulse Stimulation (TPS) uses shockwave pulses for mechanical stimulation of the brain tissue. Detailed animal evaluation conformed the experience from years of shockwave applications in other medical disciplines that the treatment is safe. There have been no negative side effect observed. Materials & Methods 6 Alzheimer's disease patients have been treated with TPS since 2010. The treatment consisted of a booster block of 6 treatment sessions within 2 weeks and one re-treatment session per month after 3 months follow-up. 6000 shockwave pulses with energy flux density of 0.2mJ/mm2 were applied in one session. Second booster treatment (6 sessions) has been administred after 2 years. Results The CERAD score was improved by 12.8% within the first 3 months. The achieved improvement was maintained for one year by monthly re-treatments. Nevertheless, afterwards the CERAD score started to decrease significantly and achieved the baseline after 12 months. Second booster treatment (6 sessions) has not been as successful as the first one. Still after another year, the CERAD score was still better than the expected disease level of an untreated patient. Conclusion The achieved results allow the assumption that more frequent booster treatments might maintain the improved CERAD score also after the first year of treatment. The current experience proves that the treatment is safe and effective. A two-center trial has been successfully completed with 35 patients. Still, further trials with larger number of patients are necessary. A placebo controlled, randomized trial is ongoing.